Identifying and developing therapeutic principles for trauma‐focused work in person‐centred and emotion‐focused therapies. Issue 4 (11th June 2019) - Murphy, David; Elliott, Robert; Carrick, Lorna
Abstract: Background: The aim of this research was to identify facilitative therapeutic principles in person‐centred and emotion‐focused therapy for working with traumatised clients in the early stages of therapy. Methods: Four cases were selected from the Strathclyde Experiential Therapy for Social Anxiety archive: one good and one poor outcome case from each therapeutic approach. Outcomes were considered good and poor based on quantitative outcome measures. Each case met DSM‐IV‐TR diagnostic criteria for both PTSD and social anxiety. We developed a new method for the identification of therapeutic principles that offers an alternative to current approaches to competency identification. Our method uses a qualitative, bottom‐up inductive process analysis. The first three sessions from each case were transcribed and independently analysed by two researchers (one blinded to the outcomes); the third researcher acted as consultant. The transcripts were analysed by focusing on session episode structure and treatment principles. Findings: Four trauma‐focused therapist principles were identified: (a) support early relationship building/alliance formation; (b) facilitate client identification and recognition of past events as trauma experiences; (c) facilitate work on traumatic sources of current experiential and interpersonal difficulties; and (d) offer self‐agency focused empathy. Conclusions: We conclude that our approach identifies and provides a new method for establishing person‐centred experiential therapy principles for early trauma‐focused work. Further research is recommended, and limitations are discussed.